Ergonomia dos ônibus urbanos: estudo de caso na cidade de Santos - Santos, Alda Paulina dos (2004)
In Santos SP, a survey was carried out among bus users, regarding these aspects, with the purpose of supplying parameters for the improvement of quality, safety and comfort for those who use public transports by bus. As public transport is the most important way of transportation, daily used by most of people, it is very important to analyze the characteristics of urban buses under the ergonomic point of view to get an important improvement of the user s quality of living. Starting from the analysis of internal internal items of chosen vehicles, such as furniture and layout, and the opinion research made among users, statistical tests were done to get conclusions and suggestions for the improvement of buses quality. Through the opinion research was possible to know better the profile of urban bus users and it concludes that despite of analyzed vehicles fulfill the requirements and regullations, many items don t answer the needs of passengers comfort.